Mycobacterium tuberculosis Zinc Metalloprotease-1 Elicits Tuberculosis-Specific Humoral Immune Response Independent of Mycobacterial Load in Pulmonary and Extra-Pulmonary Tuberculosis Patients - Vemula, Mani H.; Ganji, Rakesh; Sivangala, Ramya; Jakkala, Kiran; Gaddam, Sumanlatha; Penmetsa, Sitaramaraju; Banerjee, Sharmistha (Frontiers in Microbiology, 2016)
Conventionally, facultative intracellular pathogen, Mycobacterium tuberculosis (M.tb), the tuberculosis (TB) causing bacilli in human is cleared by cell-mediated immunity (CMI) with CD4+ T cells playing instrumental role in protective immunity, while antibody-mediated immunity (AMI) is considered non-protective. This longstanding convention has been challenged with recent evidences of increased susceptibility of hosts with compromised AMI and monoclonal antibodies conferring passive protection against TB and other intracellular pathogens. Therefore, novel approaches towards vaccine development include strategies aiming at induction of humoral response along with CMI. This necessitates the identification of mycobacterial proteins with properties of immunomodulation and strong immunogenicity. In this study, we determined the immunogenic potential of M.tb Zinc metalloprotease-1 (Zmp1), a secretory protein essential for intracellular survival and pathogenesis of M.tb. We observed that Zmp1 was secreted by in vitro grown M.tb under granuloma-like stress conditions (acidic, oxidative, iron deficiency and nutrient deprivation) and generated Th2 cytokine microenvironment upon exogenous treatment of Peripheral Blood Mononulear Cells (PBMCs) with recombinant Zmp1 (rZmp1). This was supported by recording specific and robust humoral response in TB patients in a cohort of 295. The anti-Zmp1 titers were significantly higher in TB patients (n=121) as against healthy control (n=62), household contacts (n=89) and non-specific infection controls (n=23). A significant observation of the study is the presence of equally high titers of anti-Zmp1 antibodies in a range of patients with high bacilli load (sputum bacilli load of 300+ per mL) to paucibacillary smear-negative pulmonary tuberculosis (PTB) cases. This clearly indicated the potential of Zmp1 to evoke an effective humoral response independent of mycobacterial load. Such mycobacterial proteins can be explored as antigen candidates for prime-boost vaccination strategies or extrapolated as markers for disease detection and progression.